(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article is devoted to the formation of the author’s graphic culture of future architects in the process of performing architectural graphics, considers the peculiarities of the conceptual apparatus in relation to the graphic culture of students and outlines the main directions of methodological support for the transition from a natural image of architecture to the formation of the author’s style. The purpose of the study is to find out the relationship between the performing special tasks in architectural graphics and the formation of the author’s graphic culture of future architects. The professional activity of a modern architect is multifaceted and includes all stages of design, from the development of a creative idea to its implementation. The creative design process requires technical training in this area, spatial awareness, skills and the ability to perform complex graphic constructions. Graphic literacy plays a significant role in acquiring the necessary knowledge for this. The execution of images is a necessary part of the creative process of architectural design, starting with preliminary sketches (architectural sketches), projection drawings and ending with the development of working drawings intended for construction. Architectural graphics is a means of professional representation that reveals the figurative, scale and spatial properties of an object. Modern architectural graphics is diverse and covers all types of means by which spatial forms are depicted on a plane, and also forms the professional experience in the future profession of designer, architect or builder. These tasks are solved in the course of studying Architectural Graphics. The aim of the course «Architectural Graphics» is to acquaint students with the ways of creating images of architectural objects and their parts using graphic materials, making architectural drawings, architectural sketches, sketch ideas, fore-sketches, working drawings and, most importantly, forming the author’s graphic style. Hand-drawn graphics largely express the professional handwriting and face of an architect, which is why, despite the current level of computer graphics and modelling, the ability to draw professionally is absolutely necessary for an architect to express his ideas at the stage of first thoughts, sketching and conceptualisation.